CHANGES IN OXIDATIVE STRESS BIOMARKERS IN THE FIRST-EPISODE PSYCHOSIS: A SYSTEMATIC REVIEW AND META-ANALYSIS - Ferreira Antunes Neto, Joaquim Maria; Nalesso, Ana Maria (International Journal of Scientific Research and Management (IJSRM), 2021)
The literature has shown that oxidative stress markers can indicate the degree of disease severity in untreated patients with schizophrenia. There is evidence that the excessive production of free radicals or the installation of oxidative stress can be evidenced at the time of the first-episode psychosis (FEP). Were used the Preferred Reporting Items for Systematic Reviews and Meta-analyses Guidelines to conduct a systematic literature search to detect studies comparing oxidative stress markers in FEP patients and healthy controls (HC). Twenty-one studies were obtained for inclusion in this systematic review, comprising an overall sample of 415 FEP and 392 HC for CAT (6 studies), 1293 FEP and 1279 HC for SOD (15 studies), 500 FEP and 529 HC for GPx (9 studies), 218 FEP and 228 HC for GSH (5 estudies), and 814 FEP and 852 HC for lipid peroxidation (12 studies). By analyzing the standardized mean differences, no significant differences were found between FEP and HC groups in any of the antioxidant defense system parameters assessed, despite favoring a decrease in activity of both the antioxidant and non-enzymatic enzyme systems. Lipid peroxidation levels showed a significant increase for the FEP group compared to the HC group (p < 0.0001). Heterogeneity among studies was high, with I2 values > 90%. Sensitivity analyzes were performed to obtain more homogeneous results. Significant differences were obtained for serum/plasma SOD (p < 0.0001) and lipid peroxidation (p < 0.0001) in the FEP group compared to the HC group, but still containing high heterogeneity. These results suggest that the oxidative stress biomarkers could be used to indicate the degree for the severity of the disease in untreated patients with schizophrenia.